2012
DOI: 10.1117/1.jbo.17.9.096008
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility ofin vivointravascular photoacoustic imaging using integrated ultrasound and photoacoustic imaging catheter

Abstract: Abstract. Pilot studies of in vivo combined intravascular ultrasound (IVUS) and intravascular photoacoustic (IVPA) imaging are reported. A recently introduced prototype of an integrated IVUS/IVPA imaging catheter consisting of a single-element ultrasound transducer and a light delivery system based on a single optical fiber was adapted and used for in vivo imaging of a coronary stent deployed in a rabbit's thoracic aorta in the presence of luminal blood. The results suggest that in vivo IVUS/IVPA imaging is fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 43 publications
0
34
0
1
Order By: Relevance
“…1(a)], we were able to achieve a rigid distal section length of only 16-mm, two times shorter than the previous micromotor-based endoscope 18 and to enable the catheter section to pass freely through the 3.7-mm diameter entry port of a video endoscope. Although other PA endoscopic systems [20][21][22][23][24] have been implemented with a similar proximal actuation mechanism, their imaging probes are not sheathed in a plastic tube and/or their in vivo imaging capabilities have not been demonstrated. We believe that the presented PAE system is the first PA endoscopic system that has been implemented in a fully encapsulated form and sufficiently miniaturized to be usable for endoscopic imaging via the standard instrument channel of a clinical video endoscope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1(a)], we were able to achieve a rigid distal section length of only 16-mm, two times shorter than the previous micromotor-based endoscope 18 and to enable the catheter section to pass freely through the 3.7-mm diameter entry port of a video endoscope. Although other PA endoscopic systems [20][21][22][23][24] have been implemented with a similar proximal actuation mechanism, their imaging probes are not sheathed in a plastic tube and/or their in vivo imaging capabilities have not been demonstrated. We believe that the presented PAE system is the first PA endoscopic system that has been implemented in a fully encapsulated form and sufficiently miniaturized to be usable for endoscopic imaging via the standard instrument channel of a clinical video endoscope.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] So far, the clinical potential of the technique has been investigated in various endoscopic areas. [15][16][17][18][19][20][21][22][23][24][25][26] However, the development of associated imaging devices is still at an immature stage because of technical challenges. Unlike existing ultrasonic (US) 27,28 or optical endoscopic probes, [29][30][31][32][33][34][35][36][37] PA endoscopy (PAE) requires the integration of both optical and acoustic elements in a small space.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this also allows for using US imaging information for improvements of the PA image, such as in displacement compensated averaging [6]. Hybrid PA/US imaging devices have also been demonstrated for intravascular imaging, using an imaging catheter [7]. All the mentioned implementations have in common that the used devices are rather optimized for US than for PA imaging.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31] Such probes are being developed and tested by other groups with the ultimate goal of clinical translation. 29,[32][33][34][35] In summary, this study demonstrated that PA imaging offers excellent spatial resolution, penetration, and contrast for tracking transport of a drug surrogate in the porcine vasculature. PAIS also improves the specificity for estimating drug concentrations by separating the signal from intrinsic background absorbers in cardiac tissue.…”
Section: Ultrasound and Photoacoustic Imaging Of A Dii-coated Stentmentioning
confidence: 99%